Pengelolaan Warkah Digital dan Prospek Pemanfaatannya (Studi Di Kantor Pertanahan Kota Lubuklinggau, Provinsi Sumatera Selatan) - Utami Anggraini; Slamet Muryono (Tunas Agraria, 2020)
Abstract: The ministry of ATR/BPN as a public servant requires a change in the current manual system used to store and manage land documents which is considered ineffective and inefficient because requiring a lot of time and power to distribute document. Document search is difficult and requires a long time if the documents aren’t stored appropriately. One of the land offices which have implemented digital land document management is the Land Office of Lubulinggau. The purpose of this study is to determine digital land document management and to determine the prospect of using it for land services. The research method in the present study was qualitative method with descriptive approach. The utilization prospect was analyzed by SWOT. Based on the research result digital land document management in the Land Office of Lubuklinggau used Land Document Information Application (i-Wak). The utilization prospects of digital land document management were: first, relatively faster land document search than the manual system could improve public services. Second, it was a crosscheck of data on GeoKKP and documents in the archives. Third, human resources (HR) can be trained with certain program to manage land documents. Fourth, it could be strengthened by legislations on digital documents and management by the central government. Fifth, there was electronic land document application media with central database, which was electronic land document management system (SLOKA ETNIK).Keywords: digital land document, land office, utilization prospect Intisari: Kementerian ATR/BPN sebagai pelayan publik membutuhkan suatu perubahan terhadap pengelolaan dokumen pertanahan dari manual ke digital karena dianggap tidak efektif dan tidak efisien sehingga membutuhkan waktu dan tenaga dalam proses pendistribusian dokumen. Sementara itu dalam hal pencarian dokumen sulit dilakukan apabila dokumen tidak disimpan dengan teratur. Salah satu kantor pertanahan yang telah melaksanakan kegiatan pengelolaan warkah secara digital adalah Kantor Pertanahan Kota Lubulinggau. Tujuan dari penelitian ini untuk mengetahui bagaimana pengelolaan warkah digital dan prospek pemanfaatannya untuk pelayanan pertanahan. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan deskriptif, untuk prospek pemanfaatannya dianalisis dengan analisis SWOT. Berdasarkan hasil penelitian, pengelolaan warkah digital menggunakan Aplikasi Informasi Warkah (i-Wak). Prospek Pemanfaatan yang diperoleh adalah: pertama, pencarian warkah relatif lebih cepat dibandingkan dengan sistem manual. Kedua, suatu kegiatan kroscek data yang ada di Aplikasi GeoKKP dengan dokumen yang ada di ruang arsip. Ketiga, bisa dilakukan pelatihan SDM dengan program tertentu untuk pengelolaan warkah. Keempat, dapat diperkuat dengan peraturan perundang-undangan mengenai dokumen digital oleh pemerintah pusat. Kelima, alternatif media aplikasi warkah elektronik dengan database terpusat yaitu SLOKA ETNIK.Kata Kunci: warkah digital, kantor pertanahan, prospek pemanfaatan